2013
DOI: 10.1371/journal.pone.0073150
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Ancient DNA in Sub-Fossil Insect Inclusions Preserved in ‘Anthropocene’ Colombian Copal

Abstract: Insects preserved in copal, the sub-fossilized resin precursor of amber, have potential value in molecular ecological studies of recently-extinct species and of extant species that have never been collected as living specimens. The objective of the work reported in this paper was therefore to determine if ancient DNA is present in insects preserved in copal. We prepared DNA libraries from two stingless bees (Apidae: Meliponini: Trigonisca ameliae) preserved in ‘Anthropocene’ Colombian copal, dated to ‘post-Bom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Penney et al . () showed that DNA from insect inclusions does not even survive in copal, which is immature amber, so that DNA preserved on geological timescales (millions of years) is extremely unlikely. Organelles and cell membranes have been reported from amber (Koller, Schmitt & Tischendorf, ), but even resistant macromolecules like lignin are significantly degraded (Stankiewicz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Penney et al . () showed that DNA from insect inclusions does not even survive in copal, which is immature amber, so that DNA preserved on geological timescales (millions of years) is extremely unlikely. Organelles and cell membranes have been reported from amber (Koller, Schmitt & Tischendorf, ), but even resistant macromolecules like lignin are significantly degraded (Stankiewicz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the ancestral resurrection exercise of Benner and coworkers anticipated the existence of nondigestive ribonucleases with interesting and 'unusual' activities, of which examples are currently known (Pizzo and D'Alessio, 2007). Certainly, a 'direct' validation of these reconstruction/resurrection efforts is hardly possible, as preservation of sequenceable protein or DNA in millions-of-years-old fossils is expected to be extremely uncommon (Schweitzer, 2011;Greenwalt et al, 2013;Penney et al, 2013). Nevertheless, the study of Benner and coworkers on ribonucleases (Jermann et al, 1995) and several other analogous experimental analyses (for reviews, see Benner et al, 2007;Harms and Thornton, 2010) show that although the reconstruction of ancestral sequences is unavoidably uncertain to some extent, it is to a significant degree validated at the phenotypic level by the fact that the properties of the proteins resurrected in the laboratory are typically robust and consistent with the ancestral properties expected from coherent evolutionary narratives.…”
mentioning
confidence: 99%
“…The DNA sequences obtained from the dinosaur bone fragments were shown, soon after the initial publication, to have resulted from contamination with modern human DNA (Zischler et al, 1995). Attempts to replicate the early reports of DNA from amber specimens have been unsuccessful and indicate that the environment within amber might not be particularly conducive to DNA preservation (Austin et al, 1997;Penney et al, 2013). Other reports of million-year-old DNA, such as that from the Magnolia fossil, are now similarly ascribed to modern contamination.…”
Section: Adna's Troubled Childhoodmentioning
confidence: 99%